2010
DOI: 10.1007/s00066-010-2129-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy and Internet – What Can Patients Expect?

Abstract: internet presences of radiotherapy institutions hold the chance to supply patients with professional and individualized medical information. While some websites are already using this opportunity, others show a lack of basic information or of user-friendliness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Additionally, digital interfaces for data transfer were found to be more common in university hospitals and private practices than in non-university hospitals. These findings suggested that university hospitals may have a more innovative approach than non-university hospitals, which was consistent with a previous analysis of radiotherapy institutions in 2010 [ 22 ]. By contrast, however, universities had shortcomings in providing digital alternatives for teaching.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, digital interfaces for data transfer were found to be more common in university hospitals and private practices than in non-university hospitals. These findings suggested that university hospitals may have a more innovative approach than non-university hospitals, which was consistent with a previous analysis of radiotherapy institutions in 2010 [ 22 ]. By contrast, however, universities had shortcomings in providing digital alternatives for teaching.…”
Section: Discussionsupporting
confidence: 92%
“…In the study of Nguyen et al [3], 71% of breast cancer patients searched the Internet for breast cancer-related information. In line with that, a significant number of cancer patients seen in radiation oncology departments utilize the Internet to obtain information about their cancer type [4][5][6].…”
Section: Schlüsselwörter Nebenwirkungen • Strahlentherapie • Brustkre...mentioning
confidence: 95%